PERAN EMOSI DALAM PENGAJARAN PENDlDlKANJASMANI DAN OLAHRAGA - Setyo Nugroho (LPMPP Universitas Negeri Yogyakarta, 2004)
This analysis is performed to give a description concerning the role of emotions in teaching ofphysical education and sport. Description early with definition ofemotion expressed with results from the perception ofsome happening and described also as a state of physiological and psychological imbalance. Fear, love; and rage are the three